GHGs emission and mitigation burden for power plants in western china considering N2O and SO2 removal. Issue 6 (10th April 2019) - Fu, Shijun
Abstract : Focusing on greenhouse gases (GHGs), this article explores the actual emissions and mitigation burden of coal‐fired power plants in western region of China. Utilizing the 2006 IPCC technology‐detailed methodology, this article developed a coal content‐based GHG measurement system under consideration of N2 O emission and SO2 removal, thereafter employed it to evaluate 151 power plants in western China in 2014. At regional level, the three segmented emission sources: CO2 and N2 O from coal combustion, and CO2 from sulfur content depreciation, each contributes to emission intensity at 1011.26, 8.24 and 6.09 gCO2 e/KWh, respectively. At plant‐specific level, emission intensity is very different, with an average of 1025.60 as well as an interval of 722.38–1796.67 gCO2 e/KWh, which implies large gap in mitigation burden among power plants. Comparing mitigation cost of two pathways: CCS technology and carbon market mechanism, it is verified that on average, the former induces electricity price raised by 64.84%–97.26%, while the latter only induces 8.32% upward. From mitigation burden perspective, carbon market is more feasible than CCS technology to motivate power plant to carry out GHGs abatement in the short‐run period. © 2019 American Institute of Chemical Engineers Environ Prog, 38: e13224, 2019